Indian Economy in the Post-Reform Period: An Empirical Overview of Economic Performance and Inequality - Natarajamurthy P; Vishnu.I.Raj; Anas K.T (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
The economic reforms of 1991 marked a paradigm shift in India’s economic policy, with the adoption of Liberalisation, Privatisation, and Globalisation-based policy. The economy has undergone substantial transformation since the reforms, with growth accelerating and making India one of the largest and fastest growing economies in the world. At the same time, serious concerns have arisen due to rising economic inequalities persisting and rising in the country in the post-reform period. This study addresses these concerns by examining the overall performance and the economic inequality of the Indian economy in the post-reform period. It provides an empirical analysis of economic development, as well as distributional equities, using descriptive and trend-based analyses of secondary data and relevant indicators to evaluate economic performance and economic inequalities. The study found that while India’s economic performance has improved according to conventional indicators in the post-reform period, income and wealth inequalities have markedly increased. The study highlights the need for sustained policy attention to the distributional aspects of India’s economic growth, recommending progressive taxation and legislative interventions for distributional equity.